Dual solutions for double diffusion and MHD flow analysis of micropolar nanofluids with slip boundary condition - Khan, Y.; Majeed, Afraz Hussain; Rasheed, Muhammad Afraz; Alameer, A.; Shahzad, Hasan; Irshad, Sadia; Faraz, N. (Frontiers in Physics, 2022)
In the present communication is designed to elucidate the flow attributes of micro-polar non-Newtonian liquid over stretching/shrinking surface. In addition, we have observed the stagnation aspect along with the velocity slip condition on the momentum field. Subsequently, the temperature equation is modeled by using the Fourier law of heat conduct along with a physical aspect of stratified and heat generation absorption. More transport feature is also studied by incorporating Buongiorno nanofluid model. Mathematical formulations of the given problem is endorsed in the form of an ordinary differential system after a conversation of PDEs by using similarity transformation. Solution of modeled governing equations containing physical effects is simulated by using the shooting method in conjunction with RK- Method. The significantly effects of flow parameters that associated velocity, temperature, and concentration distribution for low and upper branch solutions is revealed through graphs and tables. Quantities of engineering concern like Skin friction coefficient and Nusselt number are also compared with previous results of critical values.